Therapy-Seeking Behavior among Parents Concerned about Their Adolescent'S Substance Use. Issue 4 (October 2019) - Kang, Augustine W.; Escobar, Katherine; Tavares, Tonya; Helseth, Sarah A.; Kelly, Lourah M.; Becker, Sara J.
Background: Among the most persistent public health problems in the United States is the gap between adolescents who need therapy for a substance use (SU) disorder and those who seek therapy. The role of parental factors (e.g., impressions of the adolescent's symptoms, sociodemographic factors) has been well documented in work examining adolescent help-seeking from professionals and paraprofessionals but has not been evaluated in studies of therapy-seeking for adolescents with SU. This study's primary objective was to identify parental sociodemographic and parent-reported clinical factors associated with therapy-seeking among parents concerned about their adolescent's SU. A secondary objective was to explore reasons why parents reported not seeking therapy and whether these reasons were associated with sociodemographic and clinical variables. Methods: We conducted a survey of 411 parents of adolescents (age 12–19) who reported elevated concern about their adolescent's SU. Parents were asked whether their adolescent had a history of therapy, and those who reported no history were asked an open-ended question about reasons why they had not sought therapy. Responses were rated by 2 independent coders and used to sort parents into 3 groups: "treaters" (those who had sought therapy), "acknowledgers" (those who acknowledged their adolescent had SU problems but did not seek therapy), and "deniers" (those who denied their adolescent had SU problems). Multinomial logistic regression examined the relationship between sociodemographic and clinical factors and group membership. Results: Multivariate analyses revealed that parent-reported SU severity, internalizing distress, and externalizing behavior problems were all associated with therapy-seeking behavior, with internationalizing distress emerging as the strongest predictor. Additionally, non-Hispanic white parents were more likely to seek therapy than minority parents. Conclusions: Parent report of symptoms, especially internalizing distress, and parental race were associated with therapy-seeking behavior, highlighting opportunities for targeted outreach to engage parents in therapy.